Redesigning doctoral education in South Africa: The case for structured coursework - McKenna, Sioux; Ashwin, Paul; Negra, Diane; Onyango, Patrick; Paretti, Marie; Teelken, Christine (Critical Studies in Teaching and Learning, 2025)
It is increasingly the norm to include coursework as part of the doctoral curriculum. In this paper, academics from six countries explore how structured coursework can enhance research preparation, build scholarly communities, and develop transferable professional skills, while raising concerns about maintaining flexibility and preserving research time. Every context brings its own histories, values, and norms and so comparing experiences runs the risk of ignoring national contexts and expectations; nonetheless, this international reflection can inform contextualised deliberations about the purpose and process of coursework. Importantly, we argue that reflections are needed about what the doctorate is for and how coursework might affect the achievement of these purposes. When implemented only with the aim of decreasing time-to-completion, coursework risks falling short of its transformative potential. For coursework to enhance doctoral education, it must attend to the fundamental purpose of contributing to the frontiers of knowledge and developing responsible, independent researchers.